2010
DOI: 10.1016/j.foodchem.2010.01.063
|View full text |Cite
|
Sign up to set email alerts
|

Determination of non-polar and mid-polar monomeric oxidation products of stigmasterol during thermo-oxidation

Abstract: Oxidation products of stigmasterol were characterized by their polarity and molecular size using solid phase extraction (SPE) and high performance size exclusion (HPSEC) methods. Monomeric oxides were studied further by GC-MS and GC-FID. The focus was on identifying and quantificating non-polar and mid-polar monomeric oxides after SPE fractionation. Commercial stigmasterol was subjected to 180 ºC up to 3 hours. Six oxidation products were identified by GC-MS in the nonpolar and mid-polar monomeric fractions, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 25 publications
3
20
1
Order By: Relevance
“…In this sense, Soupas et al (35) proposed 140 °C as the key temperature in the process, since sterols behaved differently below and above this temperature. At 175-180 °C, whereas Xu et al (30) found the maximum amount of COPs at similar times as in our experiment, some other works, (14,32,36) obtained that SOPs decreased only after 40, 60 and 90 min, respectively.…”
Section: Effect Of Heating Treatmentsupporting
confidence: 82%
See 2 more Smart Citations
“…In this sense, Soupas et al (35) proposed 140 °C as the key temperature in the process, since sterols behaved differently below and above this temperature. At 175-180 °C, whereas Xu et al (30) found the maximum amount of COPs at similar times as in our experiment, some other works, (14,32,36) obtained that SOPs decreased only after 40, 60 and 90 min, respectively.…”
Section: Effect Of Heating Treatmentsupporting
confidence: 82%
“…They can also consist on steradienes and steratrienes, compounds formed from sterols, 7-ketosterols or 7-hydroxysterols (40). Using a model system consisting on pure stigmasterol heated at 180 °C for 180 min, Menéndez-Carreño et al (32), in agreement with Lampi et al (37), reported that dimeric and polymeric products contributed to 30% of stigmasterol degradation. Menéndez-Carreño's group also described a strong relationship between non-polar/mid polar and the other indicators of oxidation reactions.…”
Section: Effect Of Heating Treatmentmentioning
confidence: 84%
See 1 more Smart Citation
“…Morales et al [33] applied it for the determination of advanced oxidation in vegetable oils through the detection of fatty acids polymers. Oligomers formation during thermo-oxidation of phytosterols has also been reported [89][90][91][92] by means of HPSEC analysis.…”
Section: Oligomers/polymersmentioning
confidence: 75%
“…PS are regarded to have health-promoting properties in preventing cardiovascular diseases by inhibiting the intestinal absorption of cholesterol, accordingly, the consumption of 2 g/day of PS could reduce the risk of heart diseases by about 25 % (Kritchevsky and Chen 2005). Therefore, PS have been recently incorporated into novel foods (Koschutnig et al 2010;Menéndez-Carreño et al 2010;Lehtonen et al 2011).…”
Section: Introductionmentioning
confidence: 99%